Genetic diversity and pathogenicity of Corynespora cassiicola isolates from rubber trees and other hosts in Vietnam - Hieu N D et al (Journal of Rubber Research, 2014)
A total of 38 isolates of Corynespora cassiicola collected from rubber trees and other hosts including papaya (Papaya carica), Ecdysanthera rosea, wild mango (Irvingia malayana), white pumpkin (Benincasa cerifera) and sesame (Sesamum indicum) from different regions of vietnam were studied for genetic diversity analysis using ribosomal DNA internal transcribed spacer (rDNA ITS) sequencing and inter simple sequence repeat (ISSR) markers. A single nucleotide polymorphism at the 135th base (Cytosine/Thymine) of the rDNA-ITS regions differentiated 38 studied isolates into two groups. Meanwhile, 88 DNA bands amplified by eight ISSR primers also generated a phylogenetic tree which clustered the studied isolates into two main groups. This was harmonious from that differentiated using the sequence of rDNA-ITS.Four of these studied isolates representing two genetic clusters and hosts were subjected to pathogenicity test using detached leaf assay and artificial inoculation in glasshouse on plantlets of seven rubber clones, white pumpkin and papaya. These isolates showed different virulence on these hosts, which was displayed by the variation in the percentage disease intensity (PDI) and average infection score (AIS). Though belonging to the same genetic cluster, C. cassiicola isolated from papaya was avirulent to white pumpkin, whereas the isolate from white pumpkin was virulent to papaya. Isolates from white pumpkin and papaya were virulent to all tested rubber clones. It seemed that the genetic relationship among isolates depends on the geographical region rather than the host source.
Source Year: 2014
Keywords: C. cassiicola; Inter simple sequence repeat (ISSR); Pathogenicity; rDNA ITS sequence; Single nucleotide polymorphisms (SNPs)